MEDIA INTERAKTIF PENGENALAN KARAKTER WAYANG PANDAWA DENGAN METODE TALKING STICK PADA SISWA KELAS III SEKOLAH DASAR NEGERI JATISARI SEMARANG - Erria Dilasetiara (STEKOM PRESS, 2019)
Based on observations, the learning method used at SD N JatisariSemarang in the form of lectures, discussions, questions and answers with the book media. Learning methodswhich so far has not been implemented enough to have an impact on the level of student understanding ofmaterial taught. The method used was less successful so students felt boredand saturated. Efforts to overcome the problems of the learning process need a solutionwith new methods that can be developed. This research uses the concept of mediainteractive Talking Stick method by adding interaction and bringing interesting featuresas well as a system for better and more varied enjoyment through prominent figureshas a good character and at the same time has a history of using puppet media.From the results of the analysis, the concept of the media chosen as interactive media is character recognitionPandawa puppets in the form of a cartoon Manga (Japanese style cartoon) so it becomesmore attractive without reducing the value of local kerifan contained therein. The strength of the mediathis is modifying wayang recognition products through digital services on a system-based basiscomputers that respond to user actions, besides that the product has other advantages, namely the teachercan change or replace evaluation questions. The results are from student questionnaire data beforeusing learning media that is in the average category 41% - 60% includedin a fairly low category, while from the data the value of students after using the mediain the category 81% - 100% included in the very high category.